ANALYSIS OF AVAILABLE PROTOCOLS IN OPTICAL COMMUNICATION NETWORKS - Yusupova Zamira Zaripovna (American Journals, 2022)
Nowadays, it is difficult to imagine the whole world without optical fiber, because all the Internet is being organized through optical fibers. Their security is of great importance, cryptographic algorithms have a great place to implement it, so the protocols in optical fiber were analyzed in the article.
Keywords: Protocol, network, base, byte, ethernet, HTTP, DNS, IP, UPD.